Educare work in Ciskei with special reference to the Keiskammahoek district - Oosthuysen, Lucia (Rhodes University, Faculty of Education, Department of Education, 1989)
High drop-out rates in the sub-standards in developing countries prompted the researcher to investigate preschool education in first and third world countries, and attend to the related problem of school readiness. The rapidly expanding Educare preschool project in the rural area ot Keiskammahoek in Ciskei was investigated as an example ot community-based low-cost preschool education. A final sample of 41 children who had attended Educare Centres were matched to a control group on age, sex, primary school (where possible), and breadwinner's occupation. The Abbreviated Aptitude Test for School Beginners (standardised on Xhosa-speaking school beginners) was used to test tor significant differences between the two groups six to seven weeks atter school entry. A t-test was used on raw scores and chi-squared tests on staves. No signiticant difference was found between the means of the experimental and control groups. On a subjective rating scale for general-linguistic development and socio-emotional adjustment, no significant difference between means of the experimental and control groups was found. The experimental group's tailure to perform better than the control group, could be ascribed to various reasons, amongst others, the possible shortcoming that the pairs were not matched on intelligence, severe lack ot equipment in Educare Centres, large numbers of children in the majority of groups, uniform programmes for a wide age range, irregular attendance ot children, the low level of training of supervisors and poor home conditions. Scholastic abilities of school beginners in the Keiskammahoek District, as tested, were poor. Results deviated grossly from standardised norms. The expected percentage for the combined categories Very Weak and Weak is, tor instance, 31%; in this investigation, however, 73% of the testees fell in these two classes. Chronologically older children generally performed better. A highly significant difference existed between testees under six years and those over six years. This investigation indicated the need for better organised preschool education in rural areas in Ciskei. proposals with substantial financial implications are: Better training of para-professional staff by qualified staff. Training of qualified staff to provide expertise in preschool education in Ciskei. Provision of sufficient educational materials by Government subsidies and private sponsors. Institution of bridge classes by the Ciskei Department of Education to promote school readiness. Suggestions without financial implications include: An investigation of regulations regarding entrance age for basic education. Only in exceptional cases should children under six be admitted. Daily programmes in Educare Centres geared towards learning readiness without becoming academic. An age limit of three years for admittance to Educare Centres. Very young children should be catered for separately. Liaison between Sub A teachers and Educare staff.,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Educare; Education, Preschool -- South Africa -- Ciskei; Education, Primary -- South Africa -- Ciskei; Readiness for school -- South Africa -- Ciskei